Collocation Analysis in Kompas Digital Short Stories and Its Relevance to Indonesian Language Learning: A Semantic Study - Amelia K.D. Sinaga; Martua Reynhat Sitanggang Gusar; Renita Br. Saragih (Raja Zulkarnain Education Foundation, 2026)
This study discusses the use of collocation in digital short stories published in Kompas.com (edition 1–31 October 2025) and its relevance to Indonesian language learning in vocational high schools. Collocation as a linguistic phenomenon that shows the tendency of two or more words to appear together naturally has an important role in building meaning, atmosphere, and aesthetic effects in literary texts. This study uses a descriptive qualitative approach with documentation, reading, and note-taking techniques. Data analysis was carried out through the interactive model of Miles and Huberman and interpreted using cognitive semantic theory, especially conceptual metaphors from Lakoff and Johnson. The results show that of the 565 collocation data found, lexical collocations dominate (430 data) with the most common patterns being noun + adjective, noun + noun, and verb + noun. Meanwhile, grammatical collocations (135 data) are dominated by the pattern of verb + preposition + noun. A total of 57 collocations have metaphorical meanings, such as anger subsides, mountain in my chest, harsh criticism, and demanding life, which reflect a conceptual mapping from the concrete source domain to the abstract target domain. The results of a questionnaire to four Indonesian language teachers indicate that Kompas.com's digital short stories are considered high-quality teaching materials and relevant to the digital literacy-based curriculum, and collocation is considered important for developing students' literary text analysis skills, implicit interpretation of meaning, and creative writing skills. Thus, this study provides a theoretical contribution to the development of cognitive semantics and a practical contribution as an alternative innovative teaching material in the digital era.